2022
DOI: 10.2196/37573
|View full text |Cite
|
Sign up to set email alerts
|

Designing Studies to Inform Tobacco Harm Reduction: Learnings From an Oral Nicotine Pouch Actual Use Pilot Study

Abstract: Background Introduction of new tobacco products in the United States, including those that may be lower on the risk continuum than traditional combustible cigarettes, requires premarket authorization by the US Food and Drug Administration and information on the potential impact of the products on consumer behaviors. Efficient recruitment and data capture processes are needed to collect relevant information in a near-to-real-world environment. Objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Data from a prospective observational study conducted among 100 healthy US adults aged 21 years old or older were described by Campbell et al [94]. Participants were daily menthol and/or non-menthol cigarette smokers of at least seven cigarettes per day (CPD) who had no intention of quitting tobacco use over the eight-week study period.…”
Section: Perceptions Motivations Intentions and Actual Use Of Tfnps A...mentioning
confidence: 99%
“…Data from a prospective observational study conducted among 100 healthy US adults aged 21 years old or older were described by Campbell et al [94]. Participants were daily menthol and/or non-menthol cigarette smokers of at least seven cigarettes per day (CPD) who had no intention of quitting tobacco use over the eight-week study period.…”
Section: Perceptions Motivations Intentions and Actual Use Of Tfnps A...mentioning
confidence: 99%
“…Among the few studies assessing the longitudinal use of NPs among AS, initial evidence suggests AS may switch to these smoke-free products or use them to help reduce cigarette consumption. To date, we are aware of only two published studies of switching behavior or smoking reduction over time among AS provided with NPs [13,18]. Campbell et al (2022) provided participants with free choice among NPs in two flavors-mint or citrus-in a single nicotine level (4 mg) to use ad libitum for six weeks [18].…”
Section: Introductionmentioning
confidence: 99%
“…To date, we are aware of only two published studies of switching behavior or smoking reduction over time among AS provided with NPs [13,18]. Campbell et al (2022) provided participants with free choice among NPs in two flavors-mint or citrus-in a single nicotine level (4 mg) to use ad libitum for six weeks [18]. At the end of the study, the majority of participants reduced cigarette consumption (82%, 79 out of 97), with 16% (i.e., 15 of 97) reducing by ≥50% and 3.1% (3 out of 97) self-reporting stopping smoking.…”
Section: Introductionmentioning
confidence: 99%
“…The research that is available on ONP and switching behaviors are based on cross-sectional surveys [31], secondary analyses of results from small-sample pharmacological studies [32], and short-term (4-or 6week), site-based actual use studies [33][34][35][36]. Results from one study on ad libitum use of nicotine pouches found that using more avor varieties over 6 weeks was associated with increased cigarette reduction [36].…”
Section: Introductionmentioning
confidence: 99%